Numerical analysis of the energy absorption capacity of multi-cell square profiles under axial loads - Estrada Barbosa, Quirino (2024)
https://jcyta.cenidet.tecnm.mx/revistas/jcyta/12-Vol_7_Num_7_Enero-Junio_2024.pdf